PENGUKURAN KINERJA DENGAN BALANCED SCORECAD UNTUK MENINGKATKAN DAYA SAING PT. ABC - DANIEL SEMBIRING; ANDRI ANDRI (LPPM, 2015)
This research is intended to measure and analyze the company’s performance by four Balanced Scorecard perspectives, identifying and measuring the achievement of performance targets in each perspective. This study also measure and evaluate the implementation of the Balanced Scorecard that have done since 2004 using a questionnaire based on the Malcolm Baldrige Criteria. The results of performance measurement in the 5 years from 2010 to September 2014 shows that the average value of learning and growth perspective for workforce training 0,56%, labor productivity Rp.1,679.02 billion per person, labor turnover 3,59% and attendance rate of labor 2,11% . While the average value for the internal business process perspective with the benchmark yield production are 98.82%, 111.38% for total productivity, the value products are Rp 1,137 billion, 98.64% for product quality and 54.55% for employee suggestions. The average value of the customer's perspective to the benchmark market share are 11.69%, 36.02% for customer retention, 64.87% for customer acquisition, 9:20% for customer complaints and On Time Delivery are 92.09%. For financial perspective results the average value of ROE are 15.72%, ATO 1:50 times, ROA 4:47%, current ratio 106.85%, quick ratio 59.66%, and Net Profit Margin Ratio is 1.91%. Keywords: Balanced Scorecard, SWOT, Performance Objective